2016
DOI: 10.1186/s12944-016-0257-9
|View full text |Cite
|
Sign up to set email alerts
|

Association between ethnicity and obesity with high-density lipoprotein (HDL) function and subclass distribution

Abstract: BackgroundObesity and low high-density lipoprotein-cholesterol (HDL-C) levels are associated with cardiovascular risk. Surprisingly, despite a greater prevalence of obesity and lower HDL concentrations than white women, black South African women are relatively protected against ischaemic heart disease.MethodsWe investigated whether this apparent discrepancy may be related to different HDL function and subclass distribution in black and white, normal-weight and obese South African women (n = 40). HDL functional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 45 publications
(49 reference statements)
2
44
0
1
Order By: Relevance
“…Recently, the measurement of lipid contents in different lipoprotein subclasses has been recognized to be useful for the assessment of lipid metabolism . In adults, lipid levels in certain lipoprotein subclasses are associated with cardiovascular disease and metabolic disease . In young adults who were born preterm at very low‐birthweight, the concentration of triglyceride in the largest VLDL and of triglyceride in small HDL particles were higher than in individuals of the same age who were of average birthweight .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, the measurement of lipid contents in different lipoprotein subclasses has been recognized to be useful for the assessment of lipid metabolism . In adults, lipid levels in certain lipoprotein subclasses are associated with cardiovascular disease and metabolic disease . In young adults who were born preterm at very low‐birthweight, the concentration of triglyceride in the largest VLDL and of triglyceride in small HDL particles were higher than in individuals of the same age who were of average birthweight .…”
Section: Discussionmentioning
confidence: 99%
“…With regard to HDL particle size, previous research has indicated that obesity is associated with a decrease in the proportion of large HDL subclass, which may increase the risk of cardiovascular disease . Furthermore, the smaller HDL subclasses, which more closely correlate with HDL function and confer less risk of cardiovascular disease, are important markers of residual mortality risk for cardiovascular disease .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…80 In addition, obese women had decreased levels of large HDL compared with their normal-weight counterparts. 80 These preliminary data indicate the importance of a -Woudberg et al focussed approach on HDL subclass and functionality, which may provide further novel insights into CVD risk in African populations.…”
Section: African Populations Does Not Include Elevated Hdl-c Concentrmentioning
confidence: 99%
“…Several methods have been developed to measure TAC, and the most common of these methods are the oxygen radical absorbance capacity (ORAC), ferric reducing antioxidant power (FRAP) and the total radical trapping antioxidant potential (TRAP) [5][6][7]. A FRAP spectrophotometric assay can be performed using the method developed by Benzie and Strain [8].…”
Section: Introductionmentioning
confidence: 99%